A multisite audit to assess how women with complex social factors access and engage with maternity services. (September 2017) - Rayment-Jones, Hannah; Butler, Eleanor; Miller, Chelsie; Nay, Christine; O'Dowd, Jennifer
Abstract: Objective: to audit women with socially complex lives' documented access to and engagement with antenatal care provided by three inner city, UK maternity services in relation to birth and neonatal outcomes, and referral processes. Background: women living socially complex lives, including young mothers, recently arrived immigrants, non-English speaking, and those experiencing domestic violence, poor mental health, drug and alcohol abuse, and poverty experience high rates of morbidity, mortality and poor birth outcomes. This is associated with late access to and poor engagement with antenatal care. Method: data was collected from three separate NHS trusts data management systems for a total of 182 women living socially complex lives, between January and December 2015. Data was presented by individual trust and compared to standards derived from NICE guidelines, local trust policy and national statistic using Excel and SPSS Version 22. Tests of correlation were carried out to minimise risks of confounding factors in characteristic differences. Findings: non-English speaking women were much less likely to have accessed care within the recommended timeframes, with over 70% of the sample not booked for maternity care by 12 weeks gestation. On average 89% primiparous women across all samples had less than the recommended number of antenatal appointments. No sample met the audit criteria in terms of number of antenatal appointments attended. Data held on the perinatal data management systems for a number of outcomes and processes was largely incomplete and appeared unreliable. Conclusion: this data forms a baseline against which to assess the impact of future service developments aimed at improving access and engagement with services for women living with complex social factors. The audit identified issues with the completeness and reliability of data on the perinatal data management system. Highlights: Inequalities in birth outcomes and experiences of maternity care disproportionately affect women living socially complex lives. Pregnancies to women living in areas with the highest levels of poverty in the UK are over 50% more likely to end in stillbirth or neonatal death, and carry increased risk of premature birth, low birth weight, and maternal death. TThere is a gap in knowledge around how women access and engage with their maternity service,  multi‐disciplinary healthcare professionals, and what impact this might have on their pregnancy outcomes and experiences. Audit provides insight into the reality of women's access, engagement, and referral processes compared to national guidance for women living socially complex lives.